HLA 1–3 antigen‐mismatched related peripheral blood stem cells transplantation using low‐dose antithymocyte globulin versus unrelated cord blood transplantation. Issue 3 (3rd January 2022) - Wada, Fumiya; Watanabe, Mizuki; Konuma, Takaaki; Okabe, Motohito; Kobayashi, Shinichi; Uchida, Naoyuki; Ikegame, Kazuhiro; Tanaka, Masatsugu; Sugio, Yasuhiro; Mukae, Junichi; Onizuka, Makoto; Kawakita, Toshiro; et al.
Abstract: Little information is available regarding whether unrelated cord blood transplantation (CBT) or an HLA 1–3 antigen–mismatched related donor peripheral blood stem‐cell transplantation (PBSCT) using low‐dose anti‐thymocyte globulin (ATG) is superior as an alternative transplantation for patients who lack an HLA‐matched sibling or unrelated donor. Therefore, we evaluated 7861 patients with hematologic malignancies (aged 0 to 70 years) who received either a CBT without ATG (CBT‐no ATG, n = 7034) or an HLA 1‐3 antigen–mismatched related donor PBSCT using low‐dose ATG (PBSCT‐ATG, n = 827). CBT‐no ATG was associated with significantly better overall survival (OS) than the use of a PBSCT‐ATG (hazard ratio [HR], 0.77; p < .001), although PBSCT‐ATG patients with an HLA 1 antigen‐mismatch showed OS comparable to that in the CBT‐no ATG group. Neutrophil and platelet engraftment was significantly delayed, whereas the incidences of nonrelapse mortality, and severe graft‐versus‐host disease (GVHD) were significantly lower in the CBT‐no ATG group. The incidences of relapse and chronic GVHD were comparable between these donors. In conclusion, CBT‐no ATG may be a better alternative than HLA‐mismatched related donor PBSCT using low‐dose ATG. Notably, HLA 2‐3 antigen mismatch‐related transplantation with low‐dose ATG had significant adverse effects on transplantation outcomes.